Firm investment and monetary transmission in the euro area - Jean-Bernard Chatelain; Andrea Generale; Ignacio Hernando; Ulf Von Kalckreuth; Philip Vermeulen (European Central Bank (ECB), 2001)
We present a comparable set of results on the monetary transmission channels on firm investment for the four largest countries of the euro area (Germany, France, Italy and Spain). With particularly rich micro datasets for each country containing over 215,000 observations from 1985 to 1999, we explore what can be learned on the interest channel and broad credit channel. For each of those countries we estimate neo-classical investment relationships, explaining investment by its user cost, sales and cash flow. We find investment to be sensitive to user cost changes in all those four countries. This implies an operative interest channel in these euro area countries. We also find investment in all those countries to be quite sensitive to cash flow movements. However we find that only in Italy smaller firms react more to cash flow movements, implying that a broad credit channel might not be as pervasive in all countries
Keywords: E22; E50; 330; Investment; monetary transmission channels; user cost of capital